On the impact of style investing over institutional herding: evidence from a highly concentrated market - Gavriilidis, Konstantinos (2016)
Fund managers have been found to herd significantly in major international markets, with evidence suggesting that style investing reinforces their herding. However, research to date has not explored the herding-style relationship in highly concentrated markets, despite the impact that market concentration can confer over this relationship. This study investigates this issue in the context of Portugal using monthly funds’ portfolio-holdings and documents evidence suggesting the significant temporal dependence of monthly institutional demand which is for the most part due to herding. The significance of this dependence remains robust when controlling for several styles, as well as accounting for the entry of Portugal into the EURONEXT and the outbreak of the ongoing global crisis. Combining the above with the limited evidence of significance in the presence of the styles controlled for, the authors conclude that Portuguese fund managers herd significantly without style affecting their herding.